2021
DOI: 10.1002/ardp.202000471
|View full text |Cite
|
Sign up to set email alerts
|

New quinoxalin‐1,3,4‐oxadiazole derivatives: Synthesis, characterization, in vitro biological evaluations, and molecular modeling studies

Abstract: A new series of quinoxalin‐1,3,4‐oxadiazole (10a–l) derivatives was synthesized and evaluated against some metabolic enzymes including human carbonic anhydrase (hCA) isoenzymes I and II (carbonic anhydrases I and II), cholinesterase (acetylcholinesterase and butyrylcholinesterase), and α‐glucosidase. Obtained data revealed that all the synthesized compounds were more potent as compared with the used standard inhibitors against studied target enzymes. Among the synthesized compounds, 4‐fluoro derivative (10f) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 73 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…At 405 nm, absorbances were spectrophotometrically quanti ed. [31] One mole of substrate is hydrolyzed at a rate of one unit of α-glucosidase per minute (pH: 7.4). [32]…”
Section: Biological Assaysmentioning
confidence: 99%
“…At 405 nm, absorbances were spectrophotometrically quanti ed. [31] One mole of substrate is hydrolyzed at a rate of one unit of α-glucosidase per minute (pH: 7.4). [32]…”
Section: Biological Assaysmentioning
confidence: 99%
“…In the continuation of the work of Mirzazadeh et al in discovering new and effective inhibitors against metabolic enzymes, they reported the synthesis of new series of quinoxalin-1,3,4-oxadiazole ( 114 ) derivatives. They demonstrated their inhibitory effects against human carbonic anhydrase (hCA) isoenzymes I and II (carbonic anhydrases I and II), cholinesterase (ACHE and BCHE), and α-glucosidase [ 106 ]. All the targeted compounds displayed better enzymatic inhibitory activities than the standard inhibitors.…”
Section: Six-membered Heterocyclic Compoundsmentioning
confidence: 99%
“…Therefore, it was deduced that 1,3,4-oxadiazole could also serve as an indispensable pharmacophore for new DMI fungicides (Figure 1). In addition, 1,3,4-oxadiazole derivatives are a classic type of fivemembered heterocyclic compounds containing C, N, and O atoms, and have attracted more and more attention due to the importance of oxadiazole derivatives in medicinal chemistry and extensive biological activities, such as antiviral, [16] nematocidal, [17] antifungal, [4,18,19] antitumor, [20][21][22][23] antiinflammatory, [24] α-glucosidase inhibition, [25] and antitubercular activities. [26] Moreover, electron-donating groups (e. g., À O-and-SÀ ) linked with a heteroatomic ring would be conducive to the enhancement of the binding affinity between receptor and ligand, and thus the biological activities of the hybrids could be improved.…”
Section: Introductionmentioning
confidence: 99%